5 Deans in 5 Years: Chairs Leading Through Change - Janna L Scarborough (Academic Chairpersons Conference Proceedings, 2018)
The chair/dean relationship often has a direct impact on departmental success. What happens when the there is a change in deanship? The presenters will share their experience of having five deans in five years. Through case studies and dialogue, strategies for navigating dean transitions will be shared and examined.
Keywords: Chair/Dean Relationships; Leadership Styles; Leadership Transitions; Dean Transitions; Systemic Change